Analisis Penerapan Teknologi IoT pada Alat Peraga Rekayasa Sistem Robotik Berbasis Mikrokontroler - Wahyudi; Wulan Purnamasari (PT. Lontara Digitech Indonesia, 2025)
The application of Internet of Things (IoT) technology in microcontroller-based robotic system engineering teaching aids is an innovative solution in improving the effectiveness of vocational learning, especially in the field of mechatronics and industrial automation. This study aims to analyse the impact of using IoT-based teaching aids and microcontrollers (such as Arduino or ESP32) in improving students' understanding of robotic concepts and practical skills. The research method used a quasi-experimental experiment by comparing a control group (using conventional teaching aids) and an experimental group (using IoT teaching aids). Data were collected through practical tests, learning satisfaction questionnaires, and student performance observations. The results showed that the use of IoT props increased the understanding of robotic concepts by 25% and the speed of completing practical tasks by 30% compared to traditional methods. In addition, 85% of students stated that IoT-based teaching aids are more interactive and facilitate real-time visualisation of robotic systems through digital interfaces. However, the main challenge lies in the need for stable network infrastructure and teacher training in operating IoT devices. This study concludes that the integration of IoT in microcontroller-based robotic teaching aids has the potential to improve the quality of vocational learning, with recommendations for strengthening infrastructure support and teacher training to optimise implementation.